Analisis Pemberdayaan Perempuan Berbasis Pendidikan Melalui Program Pada Kelompok Wanita Tani Seruni - Meiliana Reva Aulia; Mustangin Mustangin; Husnawati Husnawati; Muhammad Ilham Akbar B (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to describe the empowerment process of women farmers based on the use of home yards in improving family food security in RT. 07, Jawa Village through the Seruni Women Farmers Group (KWT) program fostered by CSR PT. Adimitra Baratama Nusantara. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through interviews, observations, document studies with research informants including the CSR team of PT. Adimitra Baratama Nusantara, the Chairperson of the Seruni Women Farmers Group (KWT), and female farmer members. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. While the validity of the data uses triangulation of sources and techniques. The results of the study show that the empowerment process is carried out in three stages: (1) Awareness Stage, (2) Capacity Building Stage, and (3) Post-program Empowerment Stage. This study shows that the empowerment program for women farmers based on the use of home yards fostered by CSR PT. Adimitra Baratama Nusantara can be said to have succeeded in increasing the knowledge, skills, and independence of the community in supporting family food security to provide social and economic benefits for the community.